PRESCHOOL TEACHERS’ CLASSROOM MANAGEMENT SKILLS AND BURNOUT PERCEPTIONS - İsmail ADIGÜZEL; Cemalettin İPEK (International Journal of Eurasia Social Sciences, 2016)
In this study; the investigation of classroom management skills of preschool teachers that work in preschool education and their burnout perceptions are aimed. In the study; where classroom management skills of preschool teachers and their burnout level is investigated according the different variables (such as their marital status, professional seniority, family income level, the number of the students in their classes and the reasons of choosing teaching profession); the burnout perception of teachers is tried to be predicted from the perception of their classroom management skills as well. In this study; Classroom Management Skill Level Scale and Maslach Burnout Scale are used as two different data collection tools. Following the investigation; classroom management skill perceptions of preschool teachers depending on the reason of choosing teaching profession; while their burnout perceptions depending on the variable of professional seniority in the sub-dimension of desensitization are found to differentiate statistically at a meaningful level. On the other hand; it is observed that preschool teachers’ perceptions of burnout and classroom management skill do not differentiate statistically at a meaningful level depending on marital status, profescsional seniority, the number of the students in their classes and total family income level. In this study, also the perception of burnout level of preschool teachers in each three burnout sub-dimension are observed to be able to be predicted statistically from their perception of classroom management skills. debates on abortion site nyc abortion clinics